ABUYA MUDA WALY AL-KHALIDY - Dicky Wirianto (Kalam: Jurnal Agama dan Sosial Humaniora, 2017)
Abuya Muda Waly Al-Khalidy was one of the very important Scholars in the realm of Islamic intelectualism of the 20th century in Aceh particularly. But unfortunately, the biography of this important Scholars have not received a lot of attention. This article is an attempt to elevate him in the Islamic intellectual world particularly in Aceh.